2022
DOI: 10.2196/31752
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to the Adoption of Telemedicine During the First Year of COVID-19: Systematic Review

Abstract: Background The virulent and unpredictable nature of COVID-19 combined with a change in reimbursement mechanisms both forced and enabled the rapid adoption of telemedicine around the world. Thus, it is important to now assess the effects of this rapid adoption and to determine whether the barriers to such adoption are the same today as they were under prepandemic conditions. Objective The objective of this systematic literature review was to examine the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 67 publications
3
33
1
Order By: Relevance
“…Thus, there was an initial interest in telemedicine among participants. This might have led to a self-selection bias in favor of higher satisfaction with telemedicine from the start because patients who were more comfortable with digitalization were more likely to participate in the study [ 22 ]. Although all patients consented to undergo a video consultation, it was found that patients in the intervention group were more likely to choose a video consultation for their next follow-up appointment than those in the control group, further supporting the effect of comfortability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there was an initial interest in telemedicine among participants. This might have led to a self-selection bias in favor of higher satisfaction with telemedicine from the start because patients who were more comfortable with digitalization were more likely to participate in the study [ 22 ]. Although all patients consented to undergo a video consultation, it was found that patients in the intervention group were more likely to choose a video consultation for their next follow-up appointment than those in the control group, further supporting the effect of comfortability.…”
Section: Discussionmentioning
confidence: 99%
“…Although all patients consented to undergo a video consultation, it was found that patients in the intervention group were more likely to choose a video consultation for their next follow-up appointment than those in the control group, further supporting the effect of comfortability. Although this self-selection bias is evident for all telemedicine evaluations with a similar study design, it leads to the limitation that the data do not show results for the general population but only show results for patients with a baseline interest in telemedicine [ 22 ]. Short of forcing patients to participate in telemedicine, a procedure that appears both unethical in principle and unfeasible in clinical practice, there is no acceptable way of addressing this limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current literature focuses on how wide-scale telehealth adoption increases healthcare accessibility and may mitigate the looming physician shortage [26] , [27] , [28] , [29] . It also focuses on the disadvantages, like exacerbation of disparities in resources and quality of patient care [ 26 , 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Countries around the world have developed strategies with the aim to increase citizens' use of eHealth services, and thereby facilitate access to health and social care. Implementation and use of eHealth services has varied greatly in different parts of the world until the COVID-19 pandemic accelerated their adoption globally [1]. Several publications highlight, however, that inequalities in the access to connectivity or the lack of digital literacy may prevent certain social groups from taking advantage of eHealth services, thus risking increasing stigma or isolation for certain social groups [2][3][4].…”
Section: Introductionmentioning
confidence: 99%